Analysis Of Invoice Verification Procedures At PT Jasa Raharja (PERSERO) Magelang Branch - Rizqiana Dewi Lufi; Krisnhoe Rachmi Fitrijati; Siti Maghfiroh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Invoice verification is one of the crucial stages in the expense accounting cycle, as it serves as the basis for assessing the feasibility of transaction documents before accounting is recorded. Every expense transaction is supported by legal, complete, and accurate evidence to make the financial information generated reliable. Invoices are used as source documents that are the basis for acknowledging the company's expenses and obligations, so errors in the verification process can have an impact on inaccuracies in accounting records and the reliability of financial statements. PT Jasa Raharja (Persero) Magelang Branch, as a state-owned enterprise engaged in social insurance, handles various expenditure transactions that require precision in processing invoice documents. In its implementation, the company has implemented the Digital Document Management System (SMDD) as a means of supporting the invoice verification process that is integrated with the accounting recording system. The implementation of this digital system aims to improve the traceability of transaction documents and support the consistency of data used in the expense accounting process. This article aims to analyze the invoice verification procedures implemented at PT Jasa Raharja (Persero) Magelang Branch based on the experience of internship activities in the Finance and General Sectors. The method used is observation and implementation directly through internship activities on the invoice verification process, processed through SMDD. The results of the analysis show that the invoice verification procedure has been carried out systematically through the stages of document examination, matching invoice data with data recorded in the system, and determining the verification status before the invoice is used as the basis for accounting records. However, several obstacles were still found, such as the limitation of additional supporting documents, mismatches in transaction data, and suboptimal quality of scanned documents. These obstacles show that increasing accuracy in the verification process is still needed to maintain the reliability and accuracy of accounting records. In conclusion, although the invoice verification process has generally been implemented in accordance with established procedures, further improvements are necessary to enhance document completeness, data accuracy, and the overall reliability of accounting records.